The Perception of Senior High School Students Towards E-Learning in Bolgatanga Municipality, Ghana - Jesse Atuah; Joseph Domebale; David Laar Sanka; Cletus Azaabi; Solomon Atebi (Informatics and Software Engineering, 2025)
Electronic learning (e-learning) is a comparatively new phenomenon in Ghana and students are grappling with the idea of adopting e-learning. The Technology Acceptance Model (TAM) was used in this study to investigate the perception of senior high school students toward e-learning. The study employed the quantitative research approach. The probability sampling method was used to select a total of three hundred and sixty (360) students from a sample frame to constitute the sample size for the study. A closed-ended structured questionnaire was used to gather data on students' perceived usefulness of e-learning and students' perceived ease of use of e-learning which was then analyzed using SPSS. The results revealed student’s strong agreement that, attitude to using an e-learning system is based on student’s perception of ease of use (POEU). Similarly, the study showed that students strongly agreed that students’ perception of usefulness (PU) of e-learning systems forecasts user attitudes toward using an e-learning system.